2015
DOI: 10.5141/ecoenv.2015.007
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and lipid content of three Korean isolates of Botryococcus braunii (Trebouxiophyceae)

Abstract: Three strains of the green microalga Botryococcus braunii (JJS, KCM, and KJD) were isolated from different water bodies in Korea and grown as batch cultures in the laboratory. The effects of different growth media and temperatures on the growth rate were investigated, as well as the effect of temperature on the total lipid content and lipid profile. All three strains had the highest growth rates in BG-11 medium and at 25°C. Maximal lipid production (g L -1) was at 30°C in the JJS strain and at 25°C in the KCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Energy amount, stored in the biomass unit of cultivated microalgae was taken biom Е = 30.0 MJ/kg [20,21]. Daily amount of lipids, accumulated in the biomass of microalgae by the formula (8), the coefficient of lipid content in microalgaes biomass was taken lip k = 0,2, which, according to [21,[23][24][25], is one of the lowes possible. Density of lipids, accumulated in the biomass, was taken lip ρ = 0.85 kg/liter [26].…”
Section: Research Resultsmentioning
confidence: 99%
“…Energy amount, stored in the biomass unit of cultivated microalgae was taken biom Е = 30.0 MJ/kg [20,21]. Daily amount of lipids, accumulated in the biomass of microalgae by the formula (8), the coefficient of lipid content in microalgaes biomass was taken lip k = 0,2, which, according to [21,[23][24][25], is one of the lowes possible. Density of lipids, accumulated in the biomass, was taken lip ρ = 0.85 kg/liter [26].…”
Section: Research Resultsmentioning
confidence: 99%
“…The temperature during the testing was 27-28 o C. Lupi et al (1991) reported that Botryococcus braunii cannot grow at temperature above 32 o C, and there were no previous studies which investigated the effect of temperatures below 18 o C for the growth of Botryococcus braunii. According to Lee et al, (2015) Botryococcus microorganisms showed a variety of pH adaptability (Dayananda et al, 2017). The population of Botryococcus sp in the operation of a simple ICAF system was shown in Figure 12.…”
Section: Population Reduction Of Isochrysis Galbanamentioning
confidence: 99%
“…Among oleaginous microalgae, the colonial green alga B. braunii accumulates large quantities of hydrocarbons mainly in the extracellular space [109,110]. Cells of B. braunii associate via a unique colonial organization mediated by an extracellular matrix (ECM) mainly composed of long-chain polyacetal hydrocarbons which are cross-linked with hydrocarbons.…”
Section: Extracellular Lipidsmentioning
confidence: 99%
“…Among several extraction solvents, heptane did not damage B. braunii if it was in contact for less than 20 min. In addition, a solvent-free method of gentle pressure (i.e., “blotting”) was introduced as alternative for external oil recovery by Moheimani et al [109]. For the study of the long-term reliability of this oil recovery process, an integrated reactor was designed.…”
Section: Extracellular Lipidsmentioning
confidence: 99%